Serum soluble ST2 as a marker of renal scar in pediatric upper urinary tract infection. (August 2019) - Ohta, Naoki; Yasudo, Hiroki; Mizutani, Makoto; Matsushige, Takeshi; Fukano, Reiji; Kittaka, Setsuaki; Maehara, Kenji; Ichihara, Kiyoshi; Ohga, Shouichi; Hasegawa, Shunji
Abstract: Background and objectives: Upper urinary tract infection is the most common serious bacterial infection in childhood. Patients with upper urinary tract infection have a risk for renal scarring with subsequent complications including hypertension, proteinuria, and progressive renal failure. However, the predictive biomarkers of renal scarring in children with upper urinary tract infection are still unknown. In this study, we evaluated whether soluble ST2 levels can be biomarkers of subsequent renal scarring in patients with upper urinary tract infection. Design, setting, participants, and measurements: We retrospectively studied pediatric patients with upper urinary tract infection at a tertiary center. Twenty-eight children had an upper urinary tract infection with (n = 14) and without (n = 14) renal scarring and underwent 99mtechnetium dimercaptosuccinic acid imaging. In addition, 13 control subjects were enrolled. The clinical data and serum cytokine levels, including soluble ST2 levels, were compared between those with and without renal scars. Results: Serum soluble ST2 levels were significantly higher in the scar group than in the non-scar group, whereas there was no difference in the levels of serum interferon-γ, interleukin-6, interleukin-10, soluble tumor necrosis factor receptor 1, and transforming growth factor-β between the scar and non-scar groups. The area under the curve for differentiating between the non-scar and scar groups on the basis of measurements of serum soluble ST2 was 0.79, with a sensitivity and specificity of 92.9% and 64.3%, respectively. Conclusion: These results suggest that serum soluble ST2 levels on admission could be a useful biomarker of subsequent renal scarring in pediatric patients with upper urinary tract infection.